An ontology to represent geospatial data to support building renovation. (April 2022) - Daneshfar, Maryam; Hartmann, Timo; Rabe, Jochen
Abstract: Energy-efficient building renovation is an inter-disciplinary task and requires investigation about the building condition in the urban, environmental, and societal context. Existing literature implicitly mentions the effect of surrounding data in different stages of building renovation. Nevertheless, no conceptual framework is available for practitioners to realize the potential of such data in specific phases of the renovation. The main goal of this study is to understand: (1) based on what knowledge framework surrounding geospatial and environmental data can support building renovation projects, (2) if developing an ontology can help representing this knowledge framework, and (3) how experts and engineers involved in the renovation process can contribute to development of this knowledge framework. The results present an ontology that maps surrounding geospatial and environmental concepts for different renovation tasks and use cases within building renovation. The ontology is built upon knowledge captured from previous studies that implicitly mention the effect of these datasets in building renovation, as well as expert knowledge, brainstorming, and monitoring construction sites. Additionally, a semi-structured verification and validation workshop has been performed to incorporate insights from experts directly involved in different stages of building renovation process. This paper contributes to the body of knowledge by generating a common framework for the surrounding data required in building renovation. It has an implication in practice for engineers by providing a shared knowledge framework and for software developers by providing a basis for BIM (Building Information Modeling) and GIS (Geographic Information System) data integration for renovation purposes.